Does the reduction of inferior turbinate affect lower airway functions? - Unsal,Ozlem (2019)
Abstract Introduction: Although the nose and lungs are separate organs, numerous studies have reported that the entire respiratory system can be considered as a single anatomical and functional unit. The upper and lower airways affect each other either directly or through reflex mechanisms. Objective: In this study, we aimed to evaluate the effects of the radiofrequency ablation of persistent inferior turbinate hypertrophy on nasal and pulmonary function. Methods: Twenty-seven patients with bilateral persistent inferior turbinate hypertrophy without septal deviation were included in this study. All of the patients were evaluated using anterior rhinoscopy, nasal endoscopy, acoustic rhinometry, a visual analogue scale, and flow-sensitive spirometry on the day before and 4 months after the radiofrequency ablation procedure. Results: The post-ablation measurements revealed that the inferior turbinate ablation caused an increase in the mean cross-sectional area and volume of the nose, as well as in the forced expiratory volume in 1 s, forced vital capacity, and peak expiratory flow of the patients. These differences between the pre- and post-ablation results were statistically significant. The post-ablation visual analogue scale scores were lower when compared with the pre-ablation scores, and this difference was also statistically significant. Conclusion: This study demonstrated that the widening of the nasal passage after the reduction of the inferior turbinate size had a favorable effect on the pulmonary function tests.